2017
DOI: 10.1016/j.curtheres.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of Empirical Antibiotic Therapy for Community-Acquired Pneumonia in Children

Abstract: BackgroundCommunity-acquired pneumonia (CAP) is a leading cause of morbidity and mortality globally, responsible for more than 14% of deaths in children younger than 5 years of age. Due to difficulties with pathogen identification and diagnostics of CAP in children, targeted antimicrobial therapy is not possible, hence the widespread use of empirical antibiotics, in particular penicillins, cephalosporin, and macrolides.ObjectivesThis review aimed to address medical, societal, and political issues associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
0
8
0
2
Order By: Relevance
“…An analysis of appropriate antibiotic therapy for child hood pneumonia determined that the availability and acces sibility of WHOrecommended antibiotics is not equitable in some locations with substantial variation within countries. 19 Antibiotic use for symptoms of pneumonia varied greatly among lowincome and middleincome countries, 20 and was estimated at just 18·8% globally, in 2017, in this study. A cohort study consisting of eight sites and a mixture of urban and rural locations found that 61% of children aged 0-2 years with acute LRI received antibiotics, including 69% in rural Tanzania and 86% in urban Bangladesh.…”
Section: Discussionmentioning
confidence: 69%
“…An analysis of appropriate antibiotic therapy for child hood pneumonia determined that the availability and acces sibility of WHOrecommended antibiotics is not equitable in some locations with substantial variation within countries. 19 Antibiotic use for symptoms of pneumonia varied greatly among lowincome and middleincome countries, 20 and was estimated at just 18·8% globally, in 2017, in this study. A cohort study consisting of eight sites and a mixture of urban and rural locations found that 61% of children aged 0-2 years with acute LRI received antibiotics, including 69% in rural Tanzania and 86% in urban Bangladesh.…”
Section: Discussionmentioning
confidence: 69%
“…1 Pengamatan respons terapi sangat diperlukan karena tidak semua anak menunjukkan respons yang baik terhadap terapi awal. 2,3 Kegagalan respons pemberian antibiotika empirik di rumah sakit sekitar 9-21%. Anak yang tidak merespon terhadap antibiotika empirik kemungkinan karena adanya penyebab lain termasuk kemungkinan diagnosis banding, adanya penyakit penyerta dan adanya komplikasi pneumonia itu sendiri.…”
Section: Pendahuluanunclassified
“…Appropriate antibiotics are used for treatment of bacterial pneumonia. Effective and timely treatment together with better diagnostic tools and education prevents antibiotic resistance [20]. According to Wardlaw et al [5], treatment alone could save at least 600,000 children's lives annually at a cost of US $600 million if antibiotic treatment is universally delivered to children with pneumonia.…”
Section: Journal Of Applied Mathematicsmentioning
confidence: 99%